PRAKTIK PERJUDIAN (Studi Kasus “Judi Kupon Togel” di Kecamatan Tobelo, Kabupaten Halmahera Utara, Provinsi Maluku Utara) - Gubuino, Septiana Erike; Suwartiningsih, Sri (KRITIS, 2017)
Tobelo sub-district, Halmahera Utara (HALUT) regency, Maluku Utara (MALUT) province is one of sub-districts with full of gambling practices one of them is lottery gambling. This study is aimed at investigating and describing lottery gambling practices that people in Tobelo sub-district do based on the social and economic aspect point of view. This study was done in Tobelo sub-district, HALUT-MALUT. The method that employed in this study was descriptive qualitative. The findings show that lottery gambling practices which are often done by people in Tobelo was form of each individual meaning depends on the individual needs so that was why he did it. Besides that, there were some pros and cons opinion toward these gambling practices in Tobelo.